2019
DOI: 10.1021/acs.joc.9b02063
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Cascade Reaction by Metal-Free Aerobic Oxidation for Synthesis of Highly Functionalized 2-Amino-4-coumarinyl-5-arylpyrroles

Abstract: A novel approach has been constructed for the synthesis of two types of 2-amino-4-coumarinyl-5-arylpyrroles (ACAPs, 5 and 6) through a cascade reaction and a metal-free catalyzed aerobic oxidation reaction of arylglyoxal monohydrates 1, 1,1-enediamines (EDAMs) 2 and 3, and 4-hydroxy-2H-chromen-2-ones 4 via multicomponent reactions to produce the target compounds with good to excellent yields. Specifically, hydroxyl-substituted 2-amino-4-coumarinyl-5-arylpyrroles, that is, 2-amino-4-coumarinyl-5-aryl-6-hydroxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Consistent with numerous examples in the literature, the frequent deployment by contemporary organic chemists of α-oxoketene aminal intermediates as synthetic precursors to access a range of unique and complex heterocyclic compounds (e.g., pyrimidopyrrolopyridazines, benzo­[ f ]­imidazo­[2,1- a ]­[2,7]­naphthyridines, functionalized indoles, tetrahydroimidazo­[1,2- a ]­pyridines, spiro-oxindole, and 9-azabicyclo[3.3.1]­nonane derivatives) has rendered this motif as a versatile building block in organic synthesis. α-Oxoketene aminal derivatives are most commonly prepared by the nucleophilic substitution of α-oxoketene dithioacetals with amines, as depicted by the representative example presented in Scheme , eq 1. However, this specific methodology requires the preparation of α-oxoketene dithioacetal substrates that are typically obtained from ketone starting materials using CS 2 and a methylating agent (MeI or Me 2 SO 4 ) in the presence of a strong base (e.g., NaOH and NaH), a reaction protocol that has limited the potential for widespread application because of the use of toxic and/or volatile reagents . Alternatively, N , N ′-disubstituted ketene aminals can be derived from active methylene compounds (e.g., ethyl cyanoacetate) in a one-pot, two-step synthetic procedure involving treatment with NaH and an isothiocyanate to obtain an N , S -acetal intermediate, which is subsequently coupled with an amine in the presence of a thiocarbonyl activating reagent like EDCI (Scheme , eq 2) .…”
Section: Introductionmentioning
confidence: 61%
“…Consistent with numerous examples in the literature, the frequent deployment by contemporary organic chemists of α-oxoketene aminal intermediates as synthetic precursors to access a range of unique and complex heterocyclic compounds (e.g., pyrimidopyrrolopyridazines, benzo­[ f ]­imidazo­[2,1- a ]­[2,7]­naphthyridines, functionalized indoles, tetrahydroimidazo­[1,2- a ]­pyridines, spiro-oxindole, and 9-azabicyclo[3.3.1]­nonane derivatives) has rendered this motif as a versatile building block in organic synthesis. α-Oxoketene aminal derivatives are most commonly prepared by the nucleophilic substitution of α-oxoketene dithioacetals with amines, as depicted by the representative example presented in Scheme , eq 1. However, this specific methodology requires the preparation of α-oxoketene dithioacetal substrates that are typically obtained from ketone starting materials using CS 2 and a methylating agent (MeI or Me 2 SO 4 ) in the presence of a strong base (e.g., NaOH and NaH), a reaction protocol that has limited the potential for widespread application because of the use of toxic and/or volatile reagents . Alternatively, N , N ′-disubstituted ketene aminals can be derived from active methylene compounds (e.g., ethyl cyanoacetate) in a one-pot, two-step synthetic procedure involving treatment with NaH and an isothiocyanate to obtain an N , S -acetal intermediate, which is subsequently coupled with an amine in the presence of a thiocarbonyl activating reagent like EDCI (Scheme , eq 2) .…”
Section: Introductionmentioning
confidence: 61%
“…The 3-formylchromones 1 and 2-naphthol 2 were commercially available reagents. The heterocyclic ketene aminals (HKAs) 3 were synthesized by known literature procedures . All of the other chemicals used in the experiment were purchased from commercial sources and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…In 2020, Zi and co‐workers reported a straightforward multicomponent cascade strategy for the synthesis of a vast array of pyrrolyl‐coumarin hybrids (Scheme 4). [44] Initial optimization for the reaction condition revealed that the catalyst‐free condition was best for the reaction. Under this condition, the three‐component cascade reaction of 4‐hydroxycoumarin 17 , arylglyoxal 26 , and substituted enediamines 27 were found to deliver the desired pyrrolyl‐coumarin hybrid 28 in 80–94% yield.…”
Section: Synthesis Of 5‐membered Heterocycles Via Metal‐free Multicom...mentioning
confidence: 99%